Efektivitas Program Badung Administrasi Satu Paket (Badung Aku Sapa) pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Badung - Partini, Putu Ayu; Winaya, I Ketut; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
Badung One Package Administration Program (Badung Aku Sapa) is one of the population administration innovation programs by the Department of Population and Civil Registration of Badung Regency which aims to provide convenience to society to manage residence documents. This research uses descriptive qualitative method with data collection techniques in the form of observations, interviews and documentation. The results of this study were analysis using the effectiveness theory by Duncan which includes three indicators; achievement of objectives, integration and adaptation which shows that the implementation of the Badung One Package Administration Program (Badung Aku Sapa) has not been fully effective because there are still problems in several indicators related to the absence of a special legal basis for program implementation, inadequate socialization about the program, lack of supervision after the implementation of the program and substandard infrastructure and facilities. Key word: Effectiveness, Badung One Package Administration Program (Badung Aku Sapa)